2014
DOI: 10.1038/nrg3684
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of design principles of regulatory sequences

Abstract: Instructions for when, where and to what level each gene should be expressed are encoded within regulatory sequences. The importance of motifs recognized by DNA-binding regulators has long been known, but their extensive characterization afforded by recent technologies only partly accounts for how regulatory instructions are encoded in the genome. Here, we review recent advances in our understanding of regulatory sequences that influence transcription and go beyond the description of motifs. We discuss how und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
195
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(220 citation statements)
references
References 151 publications
4
195
0
13
Order By: Relevance
“…The in vivo protein-DNA interaction landscape is affected by multiple factors including primary sequence, DNA modifications, and chromatin accessibility, along with stabilizing and destabilizing interactions between proteins associated with the DNA (Lelli et al, 2012;Levo and Segal, 2014). Our in vitro DAP-seq assay offers a simple method to examine TF binding to its cognate target (gDNA) in a chromatin-free context, while maintaining important information related to primary genome sequence and DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo protein-DNA interaction landscape is affected by multiple factors including primary sequence, DNA modifications, and chromatin accessibility, along with stabilizing and destabilizing interactions between proteins associated with the DNA (Lelli et al, 2012;Levo and Segal, 2014). Our in vitro DAP-seq assay offers a simple method to examine TF binding to its cognate target (gDNA) in a chromatin-free context, while maintaining important information related to primary genome sequence and DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these assays employ synthetic DNA that lacks genomic DNA properties known to impact TF binding, including primary sequence context and chemical modifications, such as the widespread and tissue-specific 5-methylcytosine found in plants and animals. Efforts have been made to build synthetic oligomer pools that reflect relevant cis-element sequence (Levo and Segal, 2014) or incorporate methylation (Mann et al, 2013), but complex variation in nucleotide sequence and DNA methylation patterns ) makes it extremely challenging to fully reproduce native nuclear DNA patterns by synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…TFs can precisely identify their functional binding sites from among the other 99.8% of putative binding sites in a cellular environment in vivo . Given the multiple layers that contribute to in vivo binding (Levo and Segal 2014;Slattery et al 2014;Mathelier et al 2016;Zentner et al 2015), it is clear that DNA sequence and shape at core binding sites, which in vitro experiments have identified as determinants of DNA binding specificity (Zhao and Stormo 2011;Gordân et al 2013;Zhou et al 2015;Abe et al 2015;Levo et al 2015;Yang et al 2017), are not sufficient to explain TF binding in vivo. An important question is how TFs distinguish their functional binding sites (BSs) in one region of the genome from putative non-BSs with exactly-matched core motifs in other regions in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the proposal of DNA kinks -pointlike highly flexible domains (7) -perhaps due to formation of "DNA bubbles" (8,9). Such sequence-dependent rigidity is a property of bare dsDNA and it has been suggested that the effect can be utilized for the design of promoter sequences in order to control the DNA binding affinity of transcription factors that are sensitive to DNA bendability (10). It may also arise as the consequence of the binding of proteins to specific DNA sequences; indeed, in vivo DNA is partially covered by proteins that affect its flexibility (3,(11)(12)(13)(14) and/or its local curvature (15,16).…”
mentioning
confidence: 99%